1999
DOI: 10.1007/s004240050786
|View full text |Cite
|
Sign up to set email alerts
|

A nutrient-regulated cytosolic calcium oscillator in endocrine pancreatic glucagon-secreting cells

Abstract: We investigated the influence of nutrients on spontaneous cytosolic calcium oscillations in InR1-G9 glucagonoma cells, a model for pancreatic alpha-cells. The oscillations depended on calcium release from stores and on calcium influx, partly through voltage-dependent calcium channels. Oscillations required the presence of at least 1 mM glucose, 50 microM alanine, or 50 microM glutamine, but were terminated by higher nutrient concentrations (40 mM glucose, or above 2 mM alanine or glutamine). The effects depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
0
26
1
Order By: Relevance
“…Importantly, we demonstrate here for the first time that glucose and insulin modulate the frequency of Ca 2ϩ oscillations in clonal mouse ␣-cells. This contrasts with earlier reports in lnR1-G9 glucagonoma cells (42), where nutrients were found principally to affect the amplitude of oscillations. Although the sample sizes in both the current and an earlier (41) study were not sufficiently large to quantify the changes in primary mouse ␣-cells, such frequency modulation nonetheless provides a potential mechanism through which glucose may regulate the pulsatile release of glucagon.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, we demonstrate here for the first time that glucose and insulin modulate the frequency of Ca 2ϩ oscillations in clonal mouse ␣-cells. This contrasts with earlier reports in lnR1-G9 glucagonoma cells (42), where nutrients were found principally to affect the amplitude of oscillations. Although the sample sizes in both the current and an earlier (41) study were not sufficiently large to quantify the changes in primary mouse ␣-cells, such frequency modulation nonetheless provides a potential mechanism through which glucose may regulate the pulsatile release of glucagon.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous studies have demonstrated that the GLUTag cell line responds appropriately to the regulatory factors known to control glu gene expression and GLP-1 synthesis and secretion in primary gut endocrine cells, including cAMP/protein kinase A, glucose-dependent insulinotropic peptide, and bethanechol (26,40,50,51). Likewise, the ␣-TC-1 and InR1-G9 cell lines have been routinely used as ␣ cell models to study glu gene expression and glucagon synthesis and secretion (19,20,30,(52)(53)(54)(55)(56). In these cell lines, for example, glucagon secretion is repressed by retinol and retinoic acid (52) and activated by phorbol esters (54), cytosolic calcium oscillations are inhibited by high glucose, and glu mRNA expression and glucagon synthesis are inhibited by insulin (55).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, paracrine interactions do not suffice to explain the observed alterations of glucagon secretion. Glucose inhibits glucagon secretion from clonal glucagonreleasing cells [5,11,17], and studies of pancreatic islets and cells have provided additional evidence that glucose regulates glucagon release by a direct effect on the alpha cell [5,[8][9][10][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was recently extended, showing that Ca 2+ filling of the endoplasmic reticulum inhibits a depolarising storeoperated current that may control voltage-dependent Ca 2+ influx and glucagon release [15]. Another proposal involves glucose control of the membrane potential via stimulation of electrogenic sodium-potassium counter transport [11]. The two latter alternatives are consistent with glucose shutting off voltage-dependent Ca 2+ entry and glucagon release by hyperpolarising the alpha cell [12,14,15].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation